Kidnapped - Stevenson, Robert Louis, 1850-1894. (London, New York,Toronto : Knopf, 1994)
Presents the classic novel by Robert Louis Stevenson about a sixteen-year-old orphan who is kidnapped by his villainous uncle.
Adult.
Keywords: Disinheritance -- Fiction; Jacobites -- Fiction; Kidnapping victims -- Fiction; Teenage boys -- Fiction; Boys -- Fiction; Inheritance and succession -- Fiction; Kidnapping victims -- Fiction; Teenagers -- Fiction; Scotland -- History -- 18th century -- Fiction; Scotland -- History -- Fiction